Dependable Platform Experience and Repurchase Intention in Marketplace Apps: Evidence from Indonesian Online Consumers - Rafki, Rafnelly; Defit, Sarjon; Elfiswandi, Elfiswandi (International Review of Management and Marketing, 2026)
This study examines repurchase intention in marketplace apps by focusing on dependable platform experience, service quality, platform relationship quality, price perceptions, and deal proneness. Using survey data from 450 Indonesian marketplace-app users and partial least squares structural equation modeling, the study tests the direct effects of e-service quality, price perceptions, platform relationship quality, and deal proneness on repurchase intention, as well as the moderating role of deal proneness in the price perception–repurchase intention relationship. The findings show that e-service quality and platform relationship quality are positively associated with repurchase intention, with platform relationship quality showing the strongest effect. Price perceptions, deal proneness, and the interaction effect are not significant. The study contributes to e-marketing and service marketing research by showing that repeated marketplace use depends more on reliable digital service execution and platform relationship quality than on price-related or promotion-oriented tendencies.